2005
DOI: 10.1080/10426500590906256
|View full text |Cite
|
Sign up to set email alerts
|

Diaryl Tellurium Dihalides: FromTe-Tetracoordinated Compounds toTe-Tricoordinated Molecular Complexes

Abstract: X-ray structural studies demonstrate that diaryl tellurium diiodides can be constrained by steric factors (ortho-alkyl substituents) to adopt a trigonal pyramidal structure in preference to the expected bisphenoidal structure. DFT calculations are shown to reproduce successfully structural details of the title compounds; they allow one to predict which coordination number should be energetically favored. All compounds are chiral, but the barrier to stereomutation by intra-and intermolecular pathways (60-85 kJm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Tetra-coordinated Te IV complexes of the type R 2 TeX 2 (X = Cl, Br, I) have been extensively discussed by Beckmann and co-workers [29][30][31][32], and the distorted tetrahedral seems to be the preferential configuration for R 2 TeI 2 compounds. We can attribute the RR 0 EÁX 2 , three-coordinated MC [20,21] configuration of 6 (see discussion of compound 2), to the cleavage of the RÀTe bond occurred in the starting complex (PyH)[tmpTeI 2 ] (3), from which 5 and 6 are formed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetra-coordinated Te IV complexes of the type R 2 TeX 2 (X = Cl, Br, I) have been extensively discussed by Beckmann and co-workers [29][30][31][32], and the distorted tetrahedral seems to be the preferential configuration for R 2 TeI 2 compounds. We can attribute the RR 0 EÁX 2 , three-coordinated MC [20,21] configuration of 6 (see discussion of compound 2), to the cleavage of the RÀTe bond occurred in the starting complex (PyH)[tmpTeI 2 ] (3), from which 5 and 6 are formed.…”
Section: Resultsmentioning
confidence: 99%
“…3, does not shows the tendency of the analog complex (PyH)[mesTeI 2 ] (mes = 2,4,6-trimethylphenyl) [24] (6)) and C11ÀTe1ÀI1 (93.019(6)°), allow us to consider the species [tmpTeI 2 ] À (3) as a REÁX 2 , three-coordinated trigonalbipyramidal compound [20,21], with the two iodine atoms occupying the apical sites, and the Martin notation XÀEÀX to a TBP threecoordinated configuration (also with basis on the VSEPR theory), can be now represented by 10ÀEÀ3, according to Chart 1 [22,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectra were collected using a Waters Q-tof micro mass spectrometer. Bis(2-aminophenyl) selenide (3; Zhang et al, 2013), bis(2aminophenyl) ditelluride ( 6), and bis(2-aminophenyl) tellur-ide (7; Akiba et al, 1984;Laur et al, 2005) were prepared according to reported methods.…”
Section: Methodsmentioning
confidence: 99%
“…The axial positions are occupied by more electronegative chlorine atom while the ipso carbon atoms of the mesityl moieties together with a lone pair are placed in the equatorial positions. The steric demand of the mesityl ligand in this molecule enlarges the equatorial angle [115.34(9)°] which is comparable to 113.5(2)°in Mes 2 TeBr 2 [56]. A zero dimensional dimeric unit has been realized via CÀHÁ Á ÁCl intermolecular interactions (Fig.…”
Section: Crystal Structuresmentioning
confidence: 96%